MAKKIYAH DAN MADANIYAH DALAM AL-QUR’AN - Khairil Gufron Mursyid; Mursyidatul Awaliyah (Tarbawi, 2021)
This study adopts a qualitative approach of literature review with the deep-seated aim of understanding the various responses to the evolution and dynamics of the Quranic revelation process. The methodological process begins with data collection sourced from relevant literature, both classic and contemporary, which includes works of great scholars such as Abu al-Qasim al-Naisaburi in "Al-Tanbîh ‘ala Fadhl ‘Ulum al-Qur’an" and Imam as-Suyuthi in "al-Itqan." Collected data comprises definitions and discussions on concepts such as verses, chapters, occasions of revelation (asbabun nuzul), abrogating and abrogated (nasikh and mansukh), literal and metaphorical (haqiqat and majaz), the Quranic inimitability (i’jaz al-Qur'an), the Quranic script (rasm al-Qur'an), Quranic parables (amtsal al-Qur'an), as well as categorization into Meccan (Makkiyah) and Medinan (Madaniyah) revelations. Once the data is gathered, a systematic analysis is conducted to map and understand how these concepts have evolved and been utilized in Quranic studies. The analysis is executed by examining and comparing various perspectives from scholars, in addition to their relevance to the historical and social context of the Quran's revelation. An interpretative approach is key in the analysis, where interpretation of the data strives to respect the original text and context of its revelation, while also considering the dynamics and changes over time that influence the understanding of the text. This is especially pertinent to the understanding of Meccan and Medinan revelations.